A 5′ UTR‐mediated translational efficiency mechanism inhibits the Candida albicans morphological transition. Issue 3 (28th March 2014) - Childers, Delma S.; Mundodi, Vasanthakrishna; Banerjee, Mohua; Kadosh, David
Summary While virulence properties of Candida albicans, the most commonly isolated human fungal pathogen, are controlled by transcriptional and post‐translational mechanisms, considerably little is known about the role of post‐transcriptional, and particularly translational, mechanisms. We demonstrate that UME6, a key filament‐specific transcriptional regulator whose expression level is sufficient to determine C. albicans morphology and promote virulence, has one of the longest 5′ untranslated regions (UTRs) identified in fungi to date, which is predicted to form a complex and extremely stable secondary structure. The 5′ UTR inhibits the ability of UME6, when expressed at constitutive high levels, to drive complete hyphal growth, but does not cause a reduction in UME6 transcript. Deletion of the 5′ UTR increases C. albicans filamentation under a variety of conditions but does not affect UME6 transcript level or induction kinetics. We show that the 5′ UTR functions to inhibit Ume6 protein expression under several filament‐inducing conditions and specifically reduces association of the UME6 transcript with polysomes. Overall, our findings suggest that translational efficiency mechanisms, known to regulate diverse biological processes in bacterial and viral pathogens as well as higher eukaryotes, have evolved to inhibit and fine‐tune morphogenesis, a key virulence trait of many human fungal pathogens.